Intermolecular Conjugate Addition of Pyrroloindoline and Furoindoline Radicals to α, β‐Unsaturated Enones via Photoredox Catalysis. Issue 13 (10th September 2014) - Zhou, Shupeng; Zhang, Deliang; Sun, Yu; Li, Ruofan; Zhang, Wenhao; Li, Ang
Abstract We have developed an intermolecular conjugate addition of 3a‐pyrroloindoline/furoindoline radicals to α, β‐unsaturated enones, through visible‐light photoredox catalysis. Ir(ppy)2(dtbbpy) PF6 was found to be an effective promoter to initiate this reaction from readily available 3a‐bromopyrroloindolines/furoindolines. This method was exploited to prepare a series of indole terpenoid‐like compounds of potential biological interest. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>